Risk factors of musculoskeletal symptoms among industrial workers in Peninsular Malaysia - M. H., Nurhanisah; Sulaiman, Ruhaizin; M. Y., Athirah Diyana; Kamarudin, Khairul Manami; Che Me, Rosalam (Taylor and Francis, 2024)
Objectives. The prevalence rate of work-related musculoskeletal disorders (WMSDs) globally is notably high. There are a limited number of studies investigating WMSDs and their associated risk factors. However, there are currently no data available for WMSDs among industrial workers in Peninsular Malaysia. This study aimed to identify the prevalence of WMSDs and associated risk factors among industrial workers experiencing WMSDs through their daily working tasks. Methods. A quantitative study using a questionnaire was conducted among industrial workers from rehabilitation centres and factories in Peninsular Malaysia. The analysis of 232 participant narratives aimed to identify the correlation between job tasks and musculoskeletal pain, especially in case of repetitive and heavy handling tasks. Results. The prevalence of WMSDs among industrial workers stands at 93.1%. The results also indicate that the most affected part of the body was the lower back, with 62.1% for 7 days or more in the last year, caused by industrial workers’ job tasks. The prominent risk factors associated with body parts include gender, age, working hours and most difficult tasks with MSDs, especially in the lower back. Conclusion. This survey helps us to understand whether the workers are experiencing any discomfort, pain or disability related to workplace activities. © 2024 Central Institute for Labour Protection–National Research Institute (CIOP-PIB).